Protective Role of Nigerian Honey on Sperm indices and Testis in Sucrose-Fed Rats (Bangladesh Journal of Medical Science, 2014)
Objective: This study aimed at investigating the effect of high sucrose diet on male reproductive function and if Nigerian honey could exert a protective role. Methods: Twenty-four (24) rats were randomly divided into four equal groups of six animals and given water (control); honey (H); high sucrose solution (30%w/v) (HSS); and both high sucrose solution (30%w/v) and honey (HSS+H). Each rat on honey received a daily dose of 10ml honey/kg/5ml of distilled water. Food intake, body weight, organ weight, fasting blood glucose, LH, FSH, testosterone and sperm functions were assessed. Results: This revealed that sperm motility (p